Arguments for and against Emotions - Hitchcock, David (Człowiek i Społeczeństwo, 2026)
How surprising! People sometimes argue for an expression of emotion and sometimes argue against feeling an emotion. These arguments are not the usual sort of argument for or against a statement, so it is not obvious how to analyze them and how to evaluate them. But don’t worry! On my conception of arguments as composed of illocutionary act-types, they can be analyzed as being what they seem to be (arguments for or against a Searlian expressive). And one can evaluate the inference in arguments for expressions of emotion by means of my conception of consequence as transmission of acceptability, where acceptability is an objective status that applies to all kinds of illocutionary act-types, not just statements. And one can evaluate the inference in arguments against an emotion by means of an analogous conception of refutation as transmission of the opposite of acceptability, a status that we might call ‘rejectability’.